Atractylodes lactone compounds inhibit platelet activation. (17th February 2017) - Chen, Yizhu; Yang, Wenlong; Guo, Lingyu; Wu, Xiaolin; Zhang, Tiantian; Liu, Junling; Zhang, Junfeng
Abstract: Platelets play a crucial role in the development and progression of atherosclerosis-thrombosis and, therefore, antiplatelet drugs are widely used in the treatment of coronary artery disease. Moreover, advances in understanding the biological functions of natural plant products can provide new pharmacological strategies aimed at promoting cardiovascular health. Atractylenolide I (ATL-1), ATL-2, and ATL-3 are the major bioactive components of a Qi tonifying medicinal herb Rhizoma Atractylodis Macrocephalae ( Atractylodes macrocephala ), which is commonly used in traditional Chinese medicine (TCM). These components possess well-documented anti-inflammatory and anticancer activities, but their effects on platelet activation are still unknown. In this study, the effects of ATL on platelet function in vitro and in vivo were investigated, and the underlying mechanism was explored. We found that ATL-2 and ATL-3 but not ATL-1 diminished agonist-induced platelet aggregation and diminished adenosine triphosphate (ATP) release from dense granules. The levels of phospho-Akt (Ser473) and phospho-p38 MAPK were downregulated in the presence of ATL-2 and ATL-3. We also found that ATL-2 and ATL-3 have a similar inhibitory effect on platelet activation as acetylsalicylic acid in response to agonists. Furthermore, ATL-2 and ATL-3 diminished the spreading of human platelets on immobilized fibrinogen (Fg), delayed clot retraction in platelet-depleted plasma containing human platelets, extended first occlusion time in a mouse model of ferric chloride (FeCl3 )-induced carotid arterial thrombosis, and prolonged the bleeding time. These observations suggest that ATL-2 and ATL-3 are potential candidate therapeutic drugs for the prevention of thrombosis.